2013
DOI: 10.1038/nmeth.2600
|View full text |Cite
|
Sign up to set email alerts
|

RNA-guided gene activation by CRISPR-Cas9–based transcription factors

Abstract: Technologies for engineering synthetic transcription factors have enabled many advances in medicine and science. In contrast to existing methods based on engineering of new DNA-binding proteins, we created a Cas9-based transactivator that is targeted to DNA sequences by guide RNA molecules. Co-expression of this transactivator and combinations of guide RNAs in human cells induced specific expression of endogenous target genes, demonstrating a simple and versatile approach for RNA-guided gene activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
1,013
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,166 publications
(1,042 citation statements)
references
References 31 publications
25
1,013
2
2
Order By: Relevance
“…CRISPR interference (CRISPRi) is a recently developed tool used to study single guide RNA (gRNA)-mediated sequence-specific repression of transcription in both prokaryotic and eukaryotic cells [1][2][3][4][5]. Transcription initiation and elongation of a gene can be interfered by the presence of gRNA:DNA hetero-duplex/dCas9 (a catalytically inactive form of Cas9) complex in its promoter and exons.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…CRISPR interference (CRISPRi) is a recently developed tool used to study single guide RNA (gRNA)-mediated sequence-specific repression of transcription in both prokaryotic and eukaryotic cells [1][2][3][4][5]. Transcription initiation and elongation of a gene can be interfered by the presence of gRNA:DNA hetero-duplex/dCas9 (a catalytically inactive form of Cas9) complex in its promoter and exons.…”
Section: Dear Editormentioning
confidence: 99%
“…Transgenic worms carrying Pdpy-5::dCas9 or Pdpy-5::dCas9-KRAB and one of seven dpy-5ts-gRNAs did not exhibit obvious changes in dpy-5 expression and body length ( Figure 1F and Supplementary information, Table S1a). When all seven dpy-5ts-gRNAs (1)(2)(3)(4)(5)(6)(7) were included, suppression of dpy-5 expression and Dpy phenotype occurred ( Figure 1F and Supplementary information, Figure S1aA-S1aC and S1aE). It appeared that Pdpy-5::dCas9-KRAB and dpy5ts-gRNAs (1)(2)(3)(4)(5)(6)(7) combination showed slightly stronger effect on dpy-5 expression than that of Pdpy-5::dCas9 and dpy-5ts-gRNAs(1-7) combination, although both combinations resulted in the Dpy phenotype ( Figure 1F and Supplementary information, Figure S1aA-S1aC, S1aE and Table S1a).…”
mentioning
confidence: 99%
“…These libraries could be able to capture the full complexity of transcript isoforms instead of expressing genes independently of the endogenous regulatory context. To facilitate Cas‐9‐based gain‐of‐function screening, a synthetic activator could be constructed by fusing dCas9 with transcriptional activation domains, e.g., VP64 or p65 98. It has been shown that the delivery of multiple sgRNAs targeting at the same promoter region can improve target gene activation 99.…”
Section: Resistance Target Screening and Identificationmentioning
confidence: 99%
“…using two adjacent gRNAs with Cas9n, can efficiently introduce both indel mutations and HR events with a single-stranded DNA oligo-nucleotide donor template in mammalian cells [28,10,80]. Complete disruption of the endonuclease activities (RuvC D10A along with HNH H840A ) results in a catalytically inactive Cas9, or dead-Cas9 (dCas9) [78,79]. This has been exploited to physically block the transcriptional machinery when targeted in the promoter region of a gene of interest, coined CRISPR interference (CRISPRi) [22,34] (Fig.…”
Section: Expanding Cas9 Features Through Enzyme Engineeringmentioning
confidence: 99%